The Green Roof Microbiome: Improving Plant Survival for Ecosystem Service Delivery - Fulthorpe, Roberta; MacIvor, J. Scott; Jia, Pu; Yasui, Simone-Louise E. (Frontiers in Ecology and Evolution, 2018)
Plants are key contributors to ecosystem services delivered by green roofs in cities including stormwater capture, temperature regulation, and wildlife habitat As a result, current research has primarily focused on their growth in relationship to extensive green roof (e.g. substrates <15cm depth) ecosystem services. Green roofs are exposed to a variety of harsh abiotic factors such as intense solar radiation, wind, and isolation from ground-level habitats, making survival exceedingly difficult. Plants in natural habitats benefit from a variety of interactions with fungi and bacteria. These plant-microbial interactions improve mechanisms of survival and productivity; however, many green roof substrates are sterilized prior to installation and lack microbial communities with unstudied consequences for green roof plant health and subsequent survival and performance. In this paper, we present six hypotheses on the positive role of microbes in green roof applications. In natural and experimental systems, microbial interactions have been linked to plant (1) drought tolerance, (2) pathogen protection, (3) nutrient availability, (4) salt tolerance, (5) phytohormone production, and (6) substrate stabilization, all of which are desirable properties of green roof ecosystems. As few studies exist that directly examine these relationships on green roofs, we explore the existing ecological literature on these topics to unravel the mechanisms that could support more complex green roof ecosystem and lead to new insight into the design, performance, and broader applications in green infrastructure.